Route Planning for Mobile Care Teams using Digital Twin Technology - Andersson, Wilma; Johansson, Alexandra; Thedin Olsson, Tove; You, Sophie (My University, 2025)
The ageing global population that we are facing is significantly increasing the strain on health- care systems worldwide. Mobile care teams, a key component of the Hospitals at Home initiative in Sweden, Västra Götalandsregionen, offer a promising solution by delivering hospital-level care directly in patients’ homes. This report explores the potential of integrating Digital Twin (DT) technology to optimize the routing and coordination of these teams. By creating a real-time virtual replica of the mobile care workflow, DT technology can dynamically adjust routes based on patient status, team locations, and potential emergency calls, improving resource efficiency and healthcare in general. The proposed solution utilizes existing healthcare data systems, algorithms like TOA*, and real-time data integration to enhance care delivery. The solution also addresses challenges like scalability and workflow efficiency of today’s operations of the mobile care team unit.